Online recruitment in Portugal: theories and candidate profiles - Brandao, Catarina (2020)
Online Recruitment (OR) is a growing trend. It takes place online, using tools that enable the receipt of applications, the search for professionals, a quick triage and provision of feedback to applicants. This exploratory research aims to describe perceptions of this tool, gathering data from potential job candidates and personnel stakeholders. Data was gathered using a survey and interviews. Results show that 46% of participants had already used OR and that for 42% of the applicants it took less than a week to receive feedback from the recruiting organization. Qualitative data suggests a dominant positive appraisal of this type of recruitment. It is considered a fast method and is able to reach a wide audience. However, it is impersonal and there are doubts regarding the control over the process and the veracity of the job ads. Organizations should consider the perceptions of different stakeholders in order to optimize the process of OR.